Penerapan Metode AHP dan TOPSIS dalam Aplikasi Sistem Pendukung Keputusan Pemilihan Bibit Padi - Irma Rofni Wulandari; Tiara Herliyani; Yoga Pristiyanto; Atik Nurmasani (Progresif: Jurnal Ilmiah Komputer, 2023)
The large number of rice varieties raises problems in selecting varieties that have the potential to produce more rice and are resistant to pests and diseases. One way to help the selection of rice varieties is by using a decision support system. This study aims to implement the Analytic Hierarchy Process (AHP) and Technique for Order Performance by Similarity to Ideal Solution (TOPSIS) methods in a decision support system to determine which type of rice is superior based on existing alternatives so that it can be a reference for farmers in selecting rice seeds. AHP is used in determining the weight of the criteria, while the TOPSIS method is used for ranking alternatives. The application of the AHP and TOPSIS methods was successfully implemented with the results of testing between systems with appropriate manual calculations and based on Black Box testing the system went according to design.Keywords: Decision Support System; Analytic Hierarchy Process; Technique for Order Performance by Similarity to Ideal Solution; Rice Seeds AbstrakBanyaknya varietas padi menimbulkan permasalahan dalam pemilihan jenis varietas yang memiliki potensi untuk menghasilkan padi yang lebih banyak dan memiliki ketahanan terhadap hama dan penyakit. Salah satu cara untuk membantu pemilihan varietas padi yaitu dengan menggunakan sistem pendukung keputusan. Penelitian ini bertujuan mengimplementasikan metode Analytic Hierarchy Process (AHP) dan Technique for Order Performance by Similarity to Ideal Solution (TOPSIS) pada sistem pendukung keputusan untuk menentukan jenis padi yang lebih unggul berdasarkan alternatif yang ada sehingga dapat menjadi bahan acuan para petani dalam memilih bibit padi. AHP digunakan dalam penentuan bobot kriteria, sedangkan metode TOPSIS digunakan untuk perankingan alternatif. Penerapan metode AHP dan TOPSIS berhasil diterapkan dengan hasil pengujian antara sistem dengan perhitungan manual sesuai dan berdasar pengujian Black Box sistem berjalan sesuai dengan perancangan.Kata kunci: Sistem Penunjang Keputusan; Analytic Hierarchy Process; Technique for Order Performance by Similarity to Ideal Solution; Bibit Padi